2020
DOI: 10.1111/os.12593
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study of Total Knee Arthroplasty in Aseptic Revision Surgery: Clinical Results

Abstract: Objective To review the long‐term clinical results after revision surgery and the relationship between the different clinical variables involved with a failed total knee arthroplasty (TKA) and its evolution to provide a better understanding of the current treatment methods. Methods The present study involved 89 subjects with a failed knee arthroplasty that ended up requiring revision surgery and component replacement between 2011 and 2015. The study included patients with pain remaining after TKA and indicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Extroversion represents sociability, liveliness, and surgency; neuroticism represents emotional instability and anxiousness 10 . Previous studies have demonstrated that patients who are talkative, easygoing, cooperated, and sociable tend to actively perform functional exercise with good and continued adherence to treatment and training tasks from doctors and rehabilitation practitioners 14,18–22 . In contrast, those who were passive, controlled, depressive, and even pessimistic are inclined to be depressed and catastrophizing and thus need longer times to achieve postoperative functional targets such as 90° flexion 5,18,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extroversion represents sociability, liveliness, and surgency; neuroticism represents emotional instability and anxiousness 10 . Previous studies have demonstrated that patients who are talkative, easygoing, cooperated, and sociable tend to actively perform functional exercise with good and continued adherence to treatment and training tasks from doctors and rehabilitation practitioners 14,18–22 . In contrast, those who were passive, controlled, depressive, and even pessimistic are inclined to be depressed and catastrophizing and thus need longer times to achieve postoperative functional targets such as 90° flexion 5,18,23 .…”
Section: Discussionmentioning
confidence: 99%
“…To account for the time‐dependent loss in the primary clinical benefit as assessed shortly after surgery, the overall benefit estimate was discounted at an annual discounting rate of 3% 12 . Also, we assumed that 5% of the patients per 10 years would accept the revision, as there was a 10‐year revision rate of around 5%–10% after TKA 13,14 .…”
Section: Methodsmentioning
confidence: 99%
“…The specificity and sensitivity of the Lysholm knee scoring scale have been confirmed by clinical trials. The total score of the Lysholm knee scoring scale is 100 15 . If the score is less than 70, this means that the knee function has been significantly affected and effective treatment should be taken as soon as possible.…”
Section: Lysholm Knee Scoring Scalementioning
confidence: 99%
“…For example, the American Association of Hip and Knee Surgeons (AAHKS) recommends annual clinical and radiographic follow-up on asymptomatic patients, assuming patients with problematic symptoms will present earlier [6]. Optimization and patient satisfaction with the primary TKA is vitally important because TKA revision procedures yield less than ideal results [7]. In comparison to a primary TKA, the survivorship of TKA revisions is as low as 60%, in addition to lower satisfaction rates and worse functional scores [7].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization and patient satisfaction with the primary TKA is vitally important because TKA revision procedures yield less than ideal results [7]. In comparison to a primary TKA, the survivorship of TKA revisions is as low as 60%, in addition to lower satisfaction rates and worse functional scores [7]. Although patient dissatisfaction alone is not an indication for TKA revision, indications for such revision can be classified based on acute and chronic factors [2].…”
Section: Introductionmentioning
confidence: 99%